1999
DOI: 10.1046/j.1440-1843.1999.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell interstitial pneumonia in two hard metal workers: The role of bronchoalveolar lavage in diagnosis

Abstract: Two cases of hard metal lung disease and pathological findings of giant cell interstitial pneumonia are reported. The cases worked in different factories manufacturing hard metal parts from tungsten carbide and cobalt. Pathological specimens were obtained by percutaneous thoracoscopy and transbronchial lung biopsy. X-ray microanalysis detected only tungsten carbide in the lung specimen of one case. Bronchoalveolar lavage showed diagnostic bizarre macrophages in the lavage fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…44,[51][52][53][54][55][56][57][58][59] Diagnosis of HMLD is a challenge, as symptoms are general and often mistaken for other respiratory ailments: patients often report difficulty breathing and present with reduced lung capacity, progressive lung inflammation, and eventual fibrosis. 57,60,61 HMLD has been reported in hard metal manufacturing and oil and mining/drilling industries, where workers were exposed to WC-Co dusts or fumes on a daily basis for a number of years prior to diagnosis. 44,51,[62][63][64][65] Currently, treatments are limited and no disease-specific therapy or diagnostic tool exists.…”
Section: Risk Of Wc-co Exposure: Hard Metal Lung Disease (Hmld) Prognmentioning
confidence: 99%
See 1 more Smart Citation
“…44,[51][52][53][54][55][56][57][58][59] Diagnosis of HMLD is a challenge, as symptoms are general and often mistaken for other respiratory ailments: patients often report difficulty breathing and present with reduced lung capacity, progressive lung inflammation, and eventual fibrosis. 57,60,61 HMLD has been reported in hard metal manufacturing and oil and mining/drilling industries, where workers were exposed to WC-Co dusts or fumes on a daily basis for a number of years prior to diagnosis. 44,51,[62][63][64][65] Currently, treatments are limited and no disease-specific therapy or diagnostic tool exists.…”
Section: Risk Of Wc-co Exposure: Hard Metal Lung Disease (Hmld) Prognmentioning
confidence: 99%
“…It has recently been established that the defining characteristic of HMLD is the presence of "bizarre, cannibalistic, multinucleated giant cells" in lung biopsy specimens of workers exposed to WC-Co. 57,61,63,65,68,69 These giant cell complexes are thought to originate from macrophages which have engulfed WC-Co particles, which then stimulate inflammatory and fibrotic processes in the surrounding lung tissue. 57,63,69 In some cases, WC-Co particle "deposits" have been found in biopsy specimens, confirming causative exposure to WC-Co dust and HMLD diagnosis.…”
Section: Risk Of Wc-co Exposure: Hard Metal Lung Disease (Hmld) Prognmentioning
confidence: 99%
“…The second stated that cobalt and tungsten carbide interacted with oxygen and resulted in the augmented production of toxic activated oxygen species (13). The last reported that HMLD was strongly associated with the amino acid residue Glu-69 of the HLA-DP beta chain (14).…”
Section: Case Reportmentioning
confidence: 99%
“…16,103,109 In others, there may be increased numbers of lymphocytes, neutrophils, or eosinophils. 16,63,105,[109][110][111][112] As in other forms of ILD, it is possible that elevated eosinophils are a sign of a poor prognosis, 34,111 but this is not always so. 110 Some studies have indicated that the ratio of T4 to T8 lymphocytes in BAL is low in hard metal lung disease and in asymptomatic workers, 109 but again this is certainly not always the case, 106 and no studies have clearly shown that a determination of lymphocyte subtypes is useful in the diagnosis of hard metal lung disease.…”
Section: Laboratory Testsmentioning
confidence: 99%